Architecture and public spaces. Construction and future of the Colon Theater at Lima - Barrera, Henry (2021)
The construction of the Colón Theater meant a contribution to the urban evolution of Lima, quickly becoming an important public space for social interaction since its inauguration in 1914. The diffusion of national and international theatrical performances and films took place in its crowded interior with an audience from all social sectors. In its evolution during the 20th century, the Colón reflected, like the rest of Lima’s theaters, architectural progress. The reconstruction carried out in 1941 was no coincidence, to be in keeping with the avant-garde and the harmony of the urban environment where it was located. Through unpublished sources, this article focuses on revealing how was the link that maintained this historical monument as a public space in Lima in the last century with urban progress, until the moment when it began to lose significance and fall into oblivion.